Soluble fermentable dietary fiber attenuates age-related cognitive impairment via neuroimmune and antioxidant modulation: evidence from multilevel analyses in populations and aging mouse models - He, Yijie; Li, Jin; Cong, Lin; Li, Hui; Wu, Jiarong; Liang, Songlan; Peng, Yahui; Zhou, Yuhong; Wu, Yun (Frontiers in Immunology, 2026)
BackgroundAge-related cognitive impairment (ARCI) is an urgent public health concern with limited therapeutic options. Soluble fermentable dietary fiber (SFDF) is a safe, accessible nutritional factor that may support cognition through microglial remodeling and antioxidant defense, but its dose–response effects and cellular mechanisms remain unclear.MethodsWe combined three levels of evidence (1). In 2,350 older adults from NHANES (2011–2014), weighted regression and spline modeling assessed the association between total dietary fiber intake and cognitive performance. (2) In a D-galactose–induced aging mouse model, inulin supplementation (as a representative SFDF) was tested for effects on behavior, cytokines, and oxidative stress. (3) We analyzed an independent single-nucleus RNA-seq dataset of naturally aged mice receiving a 5% SFDF intervention to characterize microglial state remodeling.ResultsHigher total dietary fiber intake was nonlinearly associated with better cognition, with ~15 g/day as the threshold for maximal benefit. In mice, SFDF improved memory and learning, alleviated anxiety-like behavior, reduced IL-6, TNF-α, and lipid peroxidation, and enhanced antioxidant defenses. Single-nucleus analyses indicated that the 5% SFDF intervention was associated with a shift toward a reparative Mic.7 microglial subtype enriched for immune regulation and oxidative defense programs.ConclusionsThese convergent population, animal, and single-cell findings support a model in which higher total dietary fiber intake is associated with better late-life cognition, and SFDF interventions can attenuate aging-related neuroimmune activation and oxidative stress in experimental systems, highlighting dietary fiber as a scalable nutritional strategy to support healthy cognitive aging.